2017
DOI: 10.1186/s12876-017-0593-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of different doses of polyethylene glycosylated porcine glucagon-like peptide-2 on ulcerative colitis in male rats

Abstract: Background: Polyethylene glycosylated (PEGylated) porcine glucagon-like peptide-2 (pGLP-2) considerably increases half-life and stability compared with the native pGLP-2, but the effective dose for intestinal damage is still unclear. This study aims to evaluate the available dose of polyethylene glycosylated porcine glucagon-like peptide-2 (PEG-pGLP-2), a modified, long-acting form of pGLP-2 in an experimental rat model of ulcerative colitis. Methods: Thirty-five male rats were randomly assigned into five grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…As a potent regenerative agent, the R-spondin 1 protein (Rspo1) has been reported to promote repopulation of the mouse intestinal epithelium, resulting in the amelioration of inflammatory symptoms in not only DSS-induced experimental mice but also IL-10-deficient colitis model mice [51]. Porcine glucagon-like peptide-2 (pGLP-2) is expected to be a potentially effective agent against UC because of its therapeutic effect associated with increased crypt proliferation and the subsequent reduced production of inflammatory cytokines [52,53]. As therapeutic agents, the IJH-SONE68-derived EPSs are expected to have a protective effect on the colonic mucosa, with potent mitogenic activity in crypt cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a potent regenerative agent, the R-spondin 1 protein (Rspo1) has been reported to promote repopulation of the mouse intestinal epithelium, resulting in the amelioration of inflammatory symptoms in not only DSS-induced experimental mice but also IL-10-deficient colitis model mice [51]. Porcine glucagon-like peptide-2 (pGLP-2) is expected to be a potentially effective agent against UC because of its therapeutic effect associated with increased crypt proliferation and the subsequent reduced production of inflammatory cytokines [52,53]. As therapeutic agents, the IJH-SONE68-derived EPSs are expected to have a protective effect on the colonic mucosa, with potent mitogenic activity in crypt cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of flavonoids regulating the enteroendocrine system are as follows: flavonoids can stimulate the secretion of cholecystokinin (CCK), ghrelin, glucagon-like peptide (GLP-1), and glucagon-like peptide (GLP-2) [49][50][51][52]. GLP-1/2; exhibit considerable potential in treating IBD due to their ability to promote the restoration of the impaired epithelial barrier; regulate T lymphocyte differentiation and function; and modulate innate immune cells, such as macrophages and dendritic cells [53][54][55][56]. Ghrelin has also been shown to mitigate intestinal inflammation in colitis mice [57].…”
Section: The Modulation Of the Enteroendocrine Systemmentioning
confidence: 99%
“…Yang et al [98] investigated the anti-inflammatory activity of peptide-10, which has a 10 times longer half-period than teduglutide, the half-life of which is 3-5 h. They discovered that peptide-10 exhibited stronger anti-inflammatory effects than with teduglutide in mice colitis models induced by DSS. Qi et al [99] set up rat colitis models induced by DSS and observed the anti-inflammatory effect of another GLP-2 analogue (polyethylene glycosylated porcine, GLP-2), the half-life of which is 16-fold longer that of the native GLP-2. This study confirmed that the GLP-2 analogue was able to lower the inflammation score in the affected colon and enhance the level of proinflammatory cytokines.…”
Section: Glp-2mentioning
confidence: 99%